Síntese e caracterização de biomaterial a base de colágeno visando regeneração de tecidos cartilaginosos, nas áreas de medicina e odontologia - Rodrigues, Adriane Colombo Liberale (2024)
SYNTHESIS AND CHARACTERIZATION OF COLLAGEN-BASED BIOMATERIAL FOR THE REGENERATION OF CARTILAGE TISSUE, IN THE AREAS OF MEDICINE AND DENTISTRY. The treatment of injuries of cartilaginous origin is a challenge for medical and dental surgeons, due to the low healing potential of human cartilage and the degree of discomfort that these injuries cause. Surgical intervention has still been widely used in attempts to fill cartilaginous defects. Thus, there is great interest in the development of bioabsorbable biomaterials that can be used to treat and repair these injuries. Type I and II collagens are used in tissue engineering as scaffolds for the treatment of cartilage injuries, due to their biocompatibility and broad clinical approval. In this work, potentially biocompatible blend formulations with increased mechanical resistance were developed, using Type 1 Porcine Collagen, Porcine Gelatin and PLGA 82/18, to support the development of a product intended for the regeneration of cartilaginous tissues; and a cost analysis was carried out for marketing the product. 18 samples were prepared, in different proportions, with and without cross-linking with glutaraldehyde. The samples were characterized physicochemically and mechanically. The results indicated that the Porcine Gelatin and Collagen mixture is more promising than using pure collagen. The blend with PLGA increases the mechanical resistance of materials by more than 10 times while maintaining deformations of the same order or lower. The x-ray diffractograms showed that the samples have amorphous characteristics. The FTIR spectra indicated the presence of bands of functional groups characteristic of PLGA, collagen and gelatin and no peaks related to contamination were observed. In the in vitro cytotoxicity test, the samples showed no toxicity. The cost of PLGA, despite being the highest of all raw materials, is not decisive for the final value of the product. The formulations Collagen 50% + Gelatin 50%, and Blend 5: PLGA 40% + (Collagen 75% + Gelatin 25%) 60% proved to be more feasible from a manufacturing point of view, without difficulties in elaboration and conformation and presented good compression results.